Notch signaling pathway in cancer: from mechanistic insights to targeted therapies - Shi, Qingmiao; Xue, Chen; Zeng, Yifan; Yuan, Xin; Chu, Qingfei; Jiang, Shuwen; Wang, Jinzhi; Zhang, Yaqi; Zhu, Danhua; Li, Lanjuan (Signal transduction and targeted therapy, 2024)
Notch signaling, renowned for its role in regulating cell fate, organ development, and tissue homeostasis across metazoans, is highly conserved throughout evolution. The Notch receptor and its ligands are transmembrane proteins containing epidermal growth factor-like repeat sequences, typically necessitating receptor-ligand interaction to initiate classical Notch signaling transduction. Accumulating evidence indicates that the Notch signaling pathway serves as both an oncogenic factor and a tumor suppressor in various cancer types. Dysregulation of this pathway promotes epithelial-mesenchymal transition and angiogenesis in malignancies, closely linked to cancer proliferation, invasion, and metastasis. Furthermore, the Notch signaling pathway contributes to maintaining stem-like properties in cancer cells, thereby enhancing cancer invasiveness. The regulatory role of the Notch signaling pathway in cancer metabolic reprogramming and the tumor microenvironment suggests its pivotal involvement in balancing oncogenic and tumor suppressive effects. Moreover, the Notch signaling pathway is implicated in conferring chemoresistance to tumor cells. Therefore, a comprehensive understanding of these biological processes is crucial for developing innovative therapeutic strategies targeting Notch signaling. This review focuses on the research progress of the Notch signaling pathway in cancers, providing in-depth insights into the potential mechanisms of Notch signaling regulation in the occurrence and progression of cancer. Additionally, the review summarizes pharmaceutical clinical trials targeting Notch signaling for cancer therapy, aiming to offer new insights into therapeutic strategies for human malignancies.